Challenging the 'Dumb Blonde' Stereotype: A Feminist and Intersectional Analysis of Gender and Professionalism in Legally Blonde (2001) Movie - Lee, Georgia Love; Sabuin, Kezia Jade Meizie; Manullang, Petronio Pirdon; Hutagalung, Rachell Christie Anastasya (Jurnal Pendidikan Makarios, 2024)
This study examines how Legally Blonde (2001) depicts femininity using a qualitative content analysis: intelligence, and gender dynamics by applying feminist criticism, gender performativity by Judith Butler (1990) and intersectionality frameworks by Kimberlé Crenshaw (1991). In addition, the elements of the visual narratives (cinematography), such as: camerawork, tones of colors were analyzed. As the result: 1) It reveals how the movie subverts traditional gender stereotypes by showing Elle Woods’ transformation from being perceived as a “dumb blonde” to a competent lawyer, challenging societal expectations that femininity equates to a lack of intelligence. 2) It highlights the challenges women face in male-dominated professions, as seen in Elle’s experience navigating Harvard Law School while maintaining her feminine identity. 3) It focuses on how Elle’s success illustrates that professional competence and femininity are not mutually exclusive, as her journey critiques the rigid expectations placed on women in professional spaces. This research offers a detailed perspective on gender roles in media, highlighting how movies can either question or uphold societal expectations related to gender and career achievement.